Developing a novel gasification-based sludge-to-methanol utilization process and exergy-economic-environmental (3E) analysis. (15th May 2022) - Shi, Tao; Liu, Yue; Yang, Ao; Sun, Shirui; Shen, Weifeng; Ren, Jingzheng
Graphical abstract: Highlights: A systematic sludge-to-methanol process is proposed. Involved subprocesses are optimized based on sensitivity analysis. Comprehensive analysis was conducted from the perspective of 3E. Detailed implications on economic subsidy are provided. Abstract: Sewage sludge is a common waste from wastewater treatment plants in Hong Kong and conventional treatment ways like the landfilling method has been gradually abandoned considering the environmental impacts and costly land. Searching for integrating processes to well treat the sludge simultaneously achieve the energy recovery can be a good alternative way. Therefore, process design and simulation of a gasification-based sludge to methanol (STM) production was proposed in this work. It considered major subsections such as gasification, power generation, absorption, methanol synthesis, and distillation. Followed by the sensitivity analysis to optimize operational parameters, economic, environmental, and exergy (3E) analysis of STM process was conducted. The economic estimation revealed the methanol production cost is 579.62/ton and the sludge disposal cost is 39.58/ton. The calculated internal rate of return (IRR) of the process is 10.20% and 5.48%, respectively with a subsidy of 20/ton sludge and without any support. Moreover, it was found the greenhouse gas (GHG) emission was 3.21 kg eq.CO2 /kg methanol and overall exergy efficiency was 37.92%. The current work implies the great potential of STM treatment strategy, which can serve as a reference for the future sludge treatment planning.